2016
DOI: 10.1021/acs.biochem.6b00070
|View full text |Cite
|
Sign up to set email alerts
|

Substrate–Protein Interactions of Type II NADH:Quinone Oxidoreductase from Escherichia coli

Abstract: Type II NADH:quinone oxidoreductases (NDH-2s) are membrane proteins involved in respiratory chains and responsible for the maintenance of NADH/NAD(+) balance in cells. NDH-2s are the only enzymes with NADH dehydrogenase activity present in the respiratory chain of many pathogens, and thus, they were proposed as suitable targets for antimicrobial therapies. In addition, NDH-2s were also considered key players for the treatment of complex I-related neurodegenerative disorders. In this work, we explored substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Here, the absorption of both NAD + (which has an absorption maximum at 260 nm that extends to 280 nm) and NADH (maximum absorption at 340 nm) precluded identification of any changes due to nucleotide binding. Significant fluorescence changes were not observed from the flavin in either S. aureus, C. thermarum, or Escherichia coli NDH-222, monitored at 450 and 530 nm (at which wavelengths the nucleotides do not absorb).…”
Section: Resultsmentioning
confidence: 95%
“…Here, the absorption of both NAD + (which has an absorption maximum at 260 nm that extends to 280 nm) and NADH (maximum absorption at 340 nm) precluded identification of any changes due to nucleotide binding. Significant fluorescence changes were not observed from the flavin in either S. aureus, C. thermarum, or Escherichia coli NDH-222, monitored at 450 and 530 nm (at which wavelengths the nucleotides do not absorb).…”
Section: Resultsmentioning
confidence: 95%
“…The interfacial electric field has also been pointed out to affect the redox potential of enzymes. A SEIRA study of the type II NADH: Quinone Oxidoreductase from E. coli immobilized on SAM-modified gold electrodes outlined a substantial increase in the redox potential of the enzyme (~140 mV) [191]. The authors attributed this upshift in potential to an electric-field-driven stabilization of the flavin cofactor.…”
Section: Effect Of Potential Electric Fieldmentioning
confidence: 99%
“…The catalytic mechanism of NDH-2 is still unclear, even considering the available structural and functional data 4 5 6 7 8 12 . Nevertheless the gathered information showed that the two substrates bind to different sites, and that a charge-transfer complex is formed between NAD + and the reduced flavin (FADH 2 ), which is dissociated by the quinone 7 8 12 . Here, we discuss the possible roles of the conserved elements in the catalytic process ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sena et al detected, for NDH-2 from S. aureus, a charge-transfer complex formed between NAD + and the reduced flavin, which is dissociated by the quinone 7 . Recently NDH-2 from Escherichia coli was also shown to have two distinct substrate binding sites and a bound semi-protonated quinol was identified as a catalytic intermediate 8 . All these recent findings were major advances for the understanding of NDH-2, but its overall mechanism is still unclear.…”
mentioning
confidence: 99%